Seed priming technology in spice crops: A review - Jegadeeswari, C. Ushamalini, K. Arunkumar, V. (Journal of Phytology, 2019)
Seed priming is one of the important method of seed treatment is the process of controlled hydration of seeds. At the time to a level that permits the pre-germinative metabolic activity, but that prevents actual emergence of the radicle is also known as pre germination seed treatment method. Seed priming is useful for increase the speed of seed germination and uniformity of germination particularly under adverse conditions like temperature, moisture and salinity. Seeds are soaked in different solutions like various inorganic salts, sugars and polyethylene glycol (PEG) a chemically inert, high molecular weight compounds, etc. After seed priming increase in hydrolytic enzyme activity especially a-amylase, strong increase of super oxide dismutase, catalase activities and expression of certain proteins related to water stress and heat shock. During germination the primed seeds contain higher scavenging of ROS (Reactive Oxygen Species). This reviews reported the primed spices seeds or rhizomes contain abiotic stress tolerant capacities, increase the antioxidant enzyme activities like peroxidase, catalase, superoxide dismutase (SOD), polyphenol oxidase (PPO), lipoxygenase (LOX) and phenyl alanine ammonia lyase (PAL), break the seed dormancy, increase the germination percentage and early growth. This studies gives an overview about the seed priming in spice crops with relevant case studies.